On Partial Complete Controllability of Semilinear Systems - Agamirza E. Bashirov; Maher Jneid (Abstract and Applied Analysis)
Many control systems can be written as a first-order differential equation if the state space enlarged. Therefore, general conditions on controllability, stated for the first-order differential equations, are too strong for these systems. For such systems partial controllability concepts, which assume the original state space, are more suitable. In this paper, a sufficient condition for the partial complete controllability of semilinear control system is proved. The result is demonstrated through examples.